Graduate Trajectory: In-Depth Follow-up Study of Bachelor of Secondary Education Graduates at Cavite State University Carmona Campus - Jocelyn Siochi (Diversitas Journal)
The study aimed to determine the career trajectory of the 145 teacher education graduates from academic years 2020-2024 at Cavite State University Carmona Campus.  Specifically, the study determined the profile of the graduates, employment status, first job experience, relevance of first and current job in the curriculum, competencies and skills learned prior to graduation, and the suggestions to improve the curriculum.  Results revealed that most  of the participants were female, single, have not taken yet any graduate studies, and receive a monthly gross income of Php10,001 to Php15,000.  Most of them are professional licensed teachers, permanently employed in local private institutions and hold professional, technical or supervisory positions.  However, few preferred not to work due to health and personal concerns. It was also revealed that reason for accepting their first job and stayed for one year to less than two years were the salary and benefits the institution offered.  The time interval for the participants to have their first job, is less than a month and social connections played significant role in their job search process. Moreover, most participants considered their completed course to be very much related to their first and current job.  Participants suggested ways to better enhance the curriculum, such as aligning the curriculum with the content of the licensure examination,   address mismatches between the students’ specialization and the subjects to be handled in the secondary level, and  the curriculum to focus more on developing the critical thinking and problem-solving skills of the students.